Mice lacking c-fos have normal hematopoietic stem cells but exhibit altered B-cell differentiation due to an impaired bone marrow environment. - Okada, S (1994)
Mice lacking c-fos develop severe osteopetrosis with deficiencies in bone remodeling and exhibit extramedullary hematopoiesis, thymic atrophy, and altered B-cell development. In this study, we have used these mice to characterize in detail the developmental potential of hematopoietic stem cells lacking c-fos and to analyze how the lymphoid differentiation is altered. In c-fos -/- mice, B-cell numbers are reduced in the spleen, lymph nodes, and the peripheral blood as a result of a marked reduction (> 90%) in the number of clonogenic B-cell precursors. In contrast, the number and lineage distribution of myeloid progenitor cells are not affected. The thymic defects observed in a large number of these mice correlate with their health status, suggesting that this may be an indirect effect of the c-fos mutation. In vitro differentiation and bone marrow reconstitution experiments demonstrated that hematopoietic stem cells lacking c-fos can give rise to all mature myeloid as well as lymphoid cells, suggesting that the observed B lymphopenia in the mutant mice is due to an altered environment. Transplantation of wild-type bone marrow cells into newborn mutant mice resulted in the establishment of a bone marrow space and subsequent correction of the B-cell defect. These results demonstrate that hematopoietic stem cells lacking Fos have full developmental potential and that the observed defect in B-cell development is most likely due to the impaired bone marrow environment as a consequence of osteopetrosis.